Attainability Analysis for Entry Vehicles Based on Differential Evolution. (17th March 2014) - Chang, Songtao; Wang, Yongji; Liu, Lei; Wei, Xing
Abstract : Attainable region provides crucial information on mission planning of entry vehicles. In order to obtain it, a series of nonlinear optimal control problems which have similar formulations are needed to be solved. However, it is difficult to compute due to severe nonlinearity of the dynamics and various constraints. In this paper, a novel method is established to generate the attainable region at the end of the entry phase. It utilizes the parallel feature of differential evolution (DE) and the high accuracy of Chebyshev polynomial interpolation. By using the Chebyshev polynomial interpolation, the original problem is transformed to several nonlinear programming problems to facilitate employing DE. Each individual in DE's population represents a candidate point on the boundary of the attainable region. In order to lead the population to the boundary simultaneously, a scheme is devised by exploiting the parallel feature of DE. Different from conventional methods which generate one point of the boundary in each run, our proposed method generates one side of the boundary of the attainable region. A scenario is presented to evaluate the designed method and some analyses are conducted to evaluate the influence of the vehicle's design parameters on the attainable region.